2012
DOI: 10.1111/j.1600-0528.2012.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

The risk of blood exposure incidents in dental practices in the Netherlands

Abstract: Nationwide data show blood exposure incidents occur frequently in dental settings, with a considerable number of high-risk incidents. Administering anaesthetics and cleaning-up are major risk factors. There is a need to intensify measures for safe working conditions in dental care settings in the Netherlands, irrespective of the type of dental practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Data were gathered from a total of 359 undergraduates who had received the HBV vaccine as pre-adolescents, but had not undergone post-vaccination serologic testing. Such testing is recommended and proves cost-effective among healthcare personnel at a risk of infection by HBV, since they may often need prophylactic measures after accidental percutaneous and/or cutaneomucosa exposure ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were gathered from a total of 359 undergraduates who had received the HBV vaccine as pre-adolescents, but had not undergone post-vaccination serologic testing. Such testing is recommended and proves cost-effective among healthcare personnel at a risk of infection by HBV, since they may often need prophylactic measures after accidental percutaneous and/or cutaneomucosa exposure ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of HBsAg was confirmed. This poor immune response could have to do with immunosuppression or with genetic factors ( 16 , 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing studies performed with dental professionals in other countries, we observed a different situation in comparison with the one identified in this study. In Iran, 11.5% 20 of professionals were not immunized against HBV; in Spain, the estimate was 27.02% 21 ; in Italy, 17% 22 ; in the Netherlands, 12% 23 ; and in the USA, only 7.1% 24 . What may justify this high prevalence of non-vaccination or non-protection among Brazilian dental surgeons is the possibility of a gradual decline of antibody levels, from 13 to 60%, one year after the end of the immunization schedule 21 .…”
Section: Discussionmentioning
confidence: 97%
“…A recent study from Pakistan suggested to develop educational programs and to install a health department managing BEAs to lower the threshold for DHCP of reporting accidents to fight present underreporting of BEAs [ 33 ]. In a study performed in The Netherlands, it was found that 16% of the BEAs reported to a professional counselling centre were considered high-risk incidents with a risk for the transmission of HBV as well as HCV and HIV, for what post-accident measures had to be taken [ 40 ]. In this study, it was reported that the vaccination rate for HBV of Dutch dentists was 98% and that 32% of the dentists who responded to the questionnaire reported to have at least 1 BEA in the previous year.…”
Section: Introductionmentioning
confidence: 99%